Mucinous Ovarian Tumors With Anaplastic Mural Nodules: Case Report - Zou, Xinxin; Huang, Hao; Zhang, Qingyu; Ma, Zhen; Chen, Yumei; Wu, Weifeng; Fu, Aizhen (Frontiers in Medicine, 2021)
Ovarian mucinous cystic tumors may be associated with various types of mural nodules, which can be classified as benign or malignant (anaplastic carcinoma, sarcoma, carcinosarcoma). However, anaplastic malignant nodules have rarely been reported. Here, we present a case of a 35-year-old woman who presented with abdominal discomfort. Ultrasonography showed a large cystic mass in the pelvic and abdominal cavities measuring 337 mm × 242 mm. Abdominal computed tomography revealed upper anterior and posterior uterine pelvic cystic lesions based on multiple nodule partition walls and classes. During hospitalization, the patient underwent exploratory laparotomy, which revealed a poorly differentiated ovarian malignant tumor, and subsequent surgical excision was performed. The pathological analysis of the surgical samples of the right ovary revealed a mucinous ovarian tumor, while the mural nodules were classified as anaplastic carcinoma. After surgery, the patient started receiving chemotherapy. Unfortunately, the patient died 6 months later. Mucinous tumor occurring with an anaplastic carcinoma is rare, and the current diagnostic methods are not sufficient in providing and early and accurate diagnosis. Most patients are already in the advanced stage upon diagnosis, and combined with poorly differentiated pathological features, the prognosis is extremely poor. Clinicians need to improve the clinical evaluation before surgery and conduct preoperative preparation and communication to improve the prognosis of patients as much as possible.